2001
DOI: 10.1063/1.1392976
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-k dielectrics prepared by plasma-enhanced chemical vapor deposition

Abstract: Carbon-doped oxide materials (SiCOH films) with ultralow dielectric constants have been prepared by plasma-enhanced chemical vapor deposition (PECVD) from mixtures of SiCOH precursors with organic materials. The films have been characterized by Rutherford backscattering and forward recoil elastic scattering analysis, Fourier transform infrared spectroscopy and index of refraction measurements, and measurement of step heights in the films. The electrical properties of the films have been measured on metal–insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 237 publications
(141 citation statements)
references
References 2 publications
1
136
2
2
Order By: Relevance
“…Different groups have investigated the properties of such fi lms and associated deposition process dependencies [41][42][43][44][45]. We have demonstrated that it is possible to extend this family of dielectrics to k values as low as 2.0 [46][47][48], thereby providing a path for the extendibility of using these fi lms in interconnects of future generations of the Si technology.…”
Section: Sicoh Films As Low-k and Ultralow-k Dielectricsmentioning
confidence: 99%
See 3 more Smart Citations
“…Different groups have investigated the properties of such fi lms and associated deposition process dependencies [41][42][43][44][45]. We have demonstrated that it is possible to extend this family of dielectrics to k values as low as 2.0 [46][47][48], thereby providing a path for the extendibility of using these fi lms in interconnects of future generations of the Si technology.…”
Section: Sicoh Films As Low-k and Ultralow-k Dielectricsmentioning
confidence: 99%
“…As mentioned above, in order to reduce further the dielectric constant of SiCOH fi lms in a controlled way the fi lms have to be prepared as a multiphase structure, using an organic porogen together with the SiCOH precursor in the plasma [46]. It was shown that the lowest achievable dielectric constant in pSiCOH fi lms depends on the organic precursor used [47,48], as illustrated in Figure 1.17 [56]. The dielectric constant of the fi lms deposited from TMCTS with the Por1 organic precursor reached a minimum value of 2.4 when deposited at a relatively low Por1/TMCTS ratio.…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Silica materials with organic functional groups (SiO:CH) has attracted much attention because of its hydrophobicity, flexible bonding states, and low dielectric constant for the applications such as water-repellent surfaces [1][2], gas-barrier coatings [3][4], and insulating layers in microelectronic devices [5][6]. These properties can be improved when the SiO:CH films have microstructures with appropriate size and shapes.…”
Section: Introductionmentioning
confidence: 99%